Pengaruh Moralitas Individu Dan Perilaku Tidak Etis Terhadap Kecenderungan Kecurangan Dengan Komitmen Organisasi Sebagai Intervening - Risviani, Eman; Animah, Animah; Jumaidi, Lalu Takdir (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2023)
This research was conducted to examine the determinants of financial management fraudulent tendencies with organizational commitment as intervening. testing was carried out on the chairman of the mosque management and the mosque treasurer in the City of Mataram which are listed on the website database simas.kemenag.go.id totaling 274 mosques. The research sample consisted of 68 mosques, which were selected based on 2 criteria on the simas.kemenag.go.id website, namely: 1) mosques with 200 worshipers or more, 2) mosques with 20 or more administrators. Data analysis was performed using the Smart PLS application. The research findings reveal that individual morality has no effect on organizational commitment, unethical behavior has no effect on fraudulent tendencies, Individual morality has no influence on the fraud tendency and organizational commitment is not an intervening variable between individual morality and the fraudulent tendencies. While unethical behavior has an influence on organizational commitment, organizational commitment and individual morality have an influence on the fraud tendency, unethical behavior has an influence on the fraud tendency and organizational commitment is an intervening variable between unethical behavior and a fraud tendency.